Corrigendum to ‘Prediction of melanoma evolution in melanocytic nevi via artificial intelligence: A call for prospective data’ [Eur J Cancer, 119 (September 2019) Pages 30–34](S0959804919304095)(10.1016/j.ejca.2019.07.009) - Sondermann, Wiebke; Utikal, Jochen Sven; Enk, Alexander H.; Schadendorf, Dirk; Klode, Joachim; Hauschild, Axel; Weichenthal, Michael; French, Lars E.; Berking, Carola; Schilling, Bastian; Haferkamp, Sebastian; Fröhling, Stefan; et al. (European Journal of Cancer, 2019)
Dr. Titus J. Brinker regrets that he originally forgot to disclose the following potential conflict of interest: Dr. Brinker owns a company that develops mobile apps (Smart Health Heidelberg GmbH, Handschuhsheimer Landstr. 9/1, 69120 Heidelberg). Dr. Brinker asked for this corrigendum himself for the reason that a paragraph of this perspective article discusses mole monitoring apps. No third party was involved in instructing this corrigendum. Dr. Brinker would like to apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2019-12-03